Gender issues regarding low income families in Multan: An analysis through Entity Relation diagram and its precedence representation by Hierarchy Chart. - Mahmood, Shahzad; Habib, Basit; Noor, Sumaira; Mahboob, Sidra (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
The study is done to analyze the family gender issues in such families which are low income. Rigid cultural patterns have major effects on the lives of the women. Due to these cultural patterns women are considered inferior in families and society. So it is very clear that now due to such cultural patterns and customs women are stuck of in different type of gender issues. Women from low income family status have to face many restrictions and constraint during their life span. They are less empowered, not have decision making power in home. They are also to face the mobility issue due to security and due to her modesty even she has no right regarding her property, access in health facilities, fear of violence and not allowed to participate in the economic activities. All these issues and their relationship in this article is seen by using some common entities in these issues and there relevance along with this after understanding the relevance a hierarchy of these issues is developed by their dependence on each other